A STUDY: CORRELATION AMONG ENGLISH READING HABIT, INTERPERSONAL INTELLIGENCE AND READING COMPREHENSION ABILITY - putra, Reko Hary; Sinthya Pralinda; Hasrinal (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
The purpose of this study was to examine the relationships between English reading habits, intrapersonal intelligence, and students’ reading comprehension ability. A quantitative approach with a descriptive correlational design was employed. The participants consisted of 44 fourth-semester students of the English Department at IAIN Kerinci selected through total sampling. Data on English reading habits and intrapersonal intelligence were gathered using questionnaires, while a reading comprehension test measured students’ reading performance. The data were analyzed using Pearson Product Moment correlation and multiple linear regression.The findings revealed a very strong and significant correlation between English reading habits and reading comprehension (r = 0.867, p < 0.05). Intrapersonal intelligence also showed a fair and significant correlation with reading comprehension (r = 0.576, p < 0.05). Simultaneously, English reading habits and intrapersonal intelligence demonstrated a very strong and significant combined relationship with reading comprehension (R = 0.868). The adjusted R² of 0.741 indicates that both predictors contributed 74.1% to the variance in reading comprehension. Regression analysis further showed that English reading habits significantly predicted reading comprehension, whereas intrapersonal intelligence did not.